Analysis of Service Quality and Strategies from Customers’ and Franchisor’s Perspectives: A Case of The Burger House and Crunchy Fried Chicken (Nepalese Journal of Business and Management Studies, 2022)
The Burger House and Crunchy Fried Chicken is a blooming franchise model with strategically distributed outlets in major areas of the Kathmandu valley. The purpose of the study was to probe the management strategies and regulations followed by the franchisor, and the perceived service qualities of the outlet from the customer’s standpoint, further resulting in the increased brand value of the CFC. During the study, the store manager of the franchisor was interviewed to gather information about management practices and regulations mandated by the franchisor to its franchisees. Next, the customers within the outlet were selected using convenience sampling methods and were presented with a set of questionnaires to rate the perceived qualities of the CFC Sankhamul outlet. Finally, customer reviews from Google Maps were analyzed to gather customer sentiments relating to the CFC service quality. The CFC franchisor, inclusive of Mr. Basanta and the team, was found to have been actively engaged in due attainment of uniform service quality through monthly inspection, routine strategic meetings, facilitation of training, and distribution of spices and ingredients within the outlets. The study reveals that customers perceive CFC Sankhamul outlets to have higher reliability, followed by tangible factors. Similarly, CFC was perceived to have low empathetic and average responsive and assurance qualities.